Pattern of dental caries in 3-6-year-old children using decayed, missing, filled surface index and hierarchical caries pattern system: A descriptive study - G D Chandan; Sweta Saraf; Nagaveni Sangavi; Anushree Khatri (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: The dental caries status of a population group with permanent dentition is traditionally described using decayed, missing, and filled teeth or surface (DMFT or DMFS) index, and the corresponding index for the primary dentition is dmft or dmfs. dmf value alone has certain limitations; therefore, additional measures to describe dental caries are important. Poulsen and Horowitz in 1997 described a hierarchical method to determine the severity of dental caries. Aim of the Study: The aim of the study was to determine the pattern of dental caries in 3-6-year-old children using Poulsen and Horowitz hierarchical system and to assess the usefulness of this system. Methodology: Data were collected from 500, 3-6-year-old children. Dmfs was recorded according to World Health Organization criteria 2013. On the basis of the caries recordings, the dmfs score of each child was calculated and each child was assigned to one of the six zones of increasing caries severity, ranging from 0 (caries free) to 5 (most severe). Statistical Analysis Used: The collected data were tabulated and analyzed using Student's t-test, ANOVA, and Pearson's correlation coefficient. Results: The overall mean dmfs for the study population was 9.10. The distribution of children according to the severity zones of Poulsen and Horowitz indicates a very low percentage (17.8%) of caries-free children and also a high percentage of children with caries in severity zone 2 (33.4%) and 4 (18.6%). Conclusion: The Poulsen and Horowitz model gives broader aspect for the assessment of severity of dental caries in 3-6-year-old children.